The SARS-CoV-2 variants and their impacts - Akmal Shukri, Amir Muhaimin; Wang, Seok Mui; Chia, Suet Lin; Mohd Nawi, Siti Farah Alwani (Journal of Pure and Applied Microbiology, 2022)
Since the first detection of the severe acute respiratory syndrome coronavirus-2 (SARS-CoV-2), the virus remains a public health concern. Several public health measures have been implemented in an effort to curb the infections. However, the effectiveness of these strategies was threatened with the emergence of numerous SARS-CoV-2 variants in all parts of the globe, due to the persistent mutations as part of the viral evolution. Mutations that usually occur in its spike glycoprotein, allow SARS-CoV-2 to possess advantageous characteristics for its survivability and persistence. This has led to poor performance of diagnostic kits which have caused non-specific and insensitive detection of these variants, resulting in undetermined infection. The variants also have caused the increased severity of COVID-19, involving hospitalisation rates, ICU admissions, and deaths. Many have reported the vaccine-breakthrough infections and reduced effectiveness of vaccination, which is supposed to provide an effective degree of protection against COVID-19 infections. Due to these issues, this review summarises the impacts related to SARS-CoV-2 variants emergence towards the performance of diagnostic kits, transmissibility of the virus, severity of disease, and effectiveness of COVID-19 vaccines.